2004
DOI: 10.1002/ijc.20630
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk associated with genotype polymorphism of the catechol estrogen‐metabolizing genes: A multigenic study on cancer susceptibility

Abstract: Estrogen has been suggested to trigger breast cancer development via an initiating mechanism involving its metabolite, catechol estrogen (CE). To examine this hypothesis, we carried out a multigenic case-control study of 469 incident breast cancer patients and 740 healthy controls to define the role of important genes involved in the different metabolic steps that protect against the potentially harmful effects of CE metabolism. We studied the 3 genes involved in CE detoxification by conjugation reactions invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 37 publications
(49 reference statements)
11
85
0
1
Order By: Relevance
“…All previous studies [4,6,8,9] except one [7] showed that there was no overall difference between breast cancer cases and controls in the distribution of TA repeat genotypes. We found the distribution of TA repeat genotypes was significantly different between cases and controls, but the patterns were not systematic in the overall analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All previous studies [4,6,8,9] except one [7] showed that there was no overall difference between breast cancer cases and controls in the distribution of TA repeat genotypes. We found the distribution of TA repeat genotypes was significantly different between cases and controls, but the patterns were not systematic in the overall analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Adegoke et al observed that the UGT1A1*28 allele was associated with an increased risk of breast cancer among Chinese women younger than 40 years old, but not among women 40 years old or over [8]. Another study conducted in a Chinese population showed that the proportion having the UGT1A1*28 allele was similar between cases and controls [9].…”
Section: Introductionmentioning
confidence: 98%
“…Most had been invited to take part in our previous molecular epidemiological studies [17][18][19][20], aimed at defining the contribution of genotypic polymorphisms of carcinogen-and estrogen-metabolizing genes as susceptibility factors for breast cancer development in Taiwan. Genomic DNA and detailed demographic information were obtained from the patients with their consent.…”
Section: Study Cohort and Sources Of Informationmentioning
confidence: 99%
“…Estrogens initiate carcinogenesis via metabolic activation to potentially carcinogenic catechol estrogen metabolites (Yager, 2000). The principal pathway for inactivation of catechol estrogen is O-methylation by catechol-O-methyltransferase (COMT) (Cheng et al, 2005;Yager and Liehr, 1996). And SAM is the necessary methyl donor for the COMT-catalyzed reaction.…”
Section: Discussionmentioning
confidence: 99%